An analysis of training load in highly trained female football players - Winther, A. K.; Baptista, I.; Pedersen, S.; Brito, J.; Randers, M. B.; Johansen, D.; Pettersen, S. A. (PLOS ONE, 2024)
This observational study aimed to analyze external training load in highly trained female football players, comparing starters and non-starters across various cycle lengths and training days. Method: External training load [duration, total distance [TD], high-speed running distance [HSRD], sprint distance [SpD], and acceleration- and deceleration distance [AccDecdist] from 100 female football players (22.3 ± 3.7 years of age) in the Norwegian premier division were collected over two seasons using STATSports APEX. This resulted in a final dataset totaling 10498 observations after multiple imputation of missing data. Microcycle length was categorized based on the number of days between matches (2 to 7 days apart), while training days were categorized relative to match day (MD, MD+1, MD+2, MD-5, MD-4, MD-3, MD-2, MD-1). Linear mixed modeling was used to assess differences between days, and starters vs. non-starters. Results: In longer cycle lengths (5-7 days between matches), the middle of the week (usually MD-4 or MD-3) consistently exhibited the highest external training load (~21-79% of MD TD, MD HSRD, MD SpD, and MD AccDecdist); though, with the exception of duration (~108-120% of MD duration), it remained lower than MD. External training load was lowest on MD+2 and MD-1 (~1-37% of MD TD, MD HSRD, MD SpD, MD AccDecdist, and ~73-88% of MD peak speed). Non-starters displayed higher loads (~137-400% of starter TD, HSRD, SpD, AccDecdist) on MD+2 in cycles with 3 to 7 days between matches, with non-significant differences (~76-116%) on other training days. Conclusion: Loading patterns resemble a pyramid or skewed pyramid during longer cycle lengths (5-7 days), with higher training loads towards the middle compared to the start and the end of the cycle. Non-starters displayed slightly higher loads on MD+2, with no significant load differentiation from MD-5 onwards.